How to read the air - Mengestu, Dinaw, 1978- (New York : Riverhead Books, 2010)
Leaving behind his marriage and job in New York, Jonas, the son of E thiopian immigrants, sets out to retrace his mother and father's trip a nd weave together a family history that will take him from the war-torn Ethiopia of his parents' youth to his life in the America of today.
Keywords: Children of immigrants -- Fiction; Ethiopians -- United States -- Fiction